There is no Planet B - Panayides, Angelos (My University, 2024)
The UDA’s prestigious annual design competition allows participants to exhibit their finest posters, which the UDA will preserve as historical artifacts. Participants are encouraged to submit their top commercial posters for clients, experimental posters for their creative endeavors, and environmental awareness posters to advocate for environmental preservation.
Keywords: exhibition catalogue